ASSESSMENT OF THE LARVICIDAL POTENTIAL OF BACILLUS THURINGIENSIS ISOLATES FROM SOIL AGAINST CULEX QUINQUIFASCIATUS (FUDMA JOURNAL OF SCIENCES, 2022)
Environmental hazard and detrimental health effects associated with usage of chemical insecticides has made the search for a safer alternative means of controlling disease vectors and pest necessary. In this study, the larvicidal potential of Bacillus thuringiensis isolates against Culex quinquefasciatus was evaluated. B. thuringiensis were isolated and characterized from different organic rich soils collected from various locations in Zaria, Kaduna State, Nigeria. The larvicidal potential of the isolates against Cx. quinquefasciatus larvae was conducted by exposing the larvae to spore crystal mixture at 50, 75 and 100 ppm concentrations. Ten larvae of Cx. quinquefasciatus were exposed to each concentration and the test was conducted in triplicates. Probit analysis was used to determine the LC50 (concentration that kills 50% of the exposed larvae) for each of concentrations assessed. For 100 ppm concentration, the mean mortality of the larvae was found to be between 33.33% and 96.67%. As for 75 ppm concentration, mean mortality range of 73.33% and 23.33% was observed while mean mortality range of 53.33% and 10.0% was observed for 50 ppm concentration. The LC50 was estimated to be between 148.73 ppm and 39.81 ppm. The results of this research show that B. thuringiensis isolated from organic rich soil samples in Zaria has promising larvicidal potential in the control of Cx. quinquifasciatus larvae; hence, reducing number of adult mosquitoes that serve as vector of diseases.
Keywords: Bacillus thuringiensis, Culex quinquifasciatus, Larvicidal, soil, activity